ANALISIS TINGKAT KEDISIPLINAN BELAJAR SISWA KELAS V SD NEGERI LIMBANGAN KERSANA KABUPATEN BREBES - Fakri Fadilah; Veryliana Purnamasari; Ervina Eka Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background that prompted this research was that the learning discipline of class V students at SD Negeri 01 Limbangan Kersana, Brebes Regency, was still relatively low. There are still students who come in late either during the first period of class or after the break and there are many textbooks that have been deliberately left in desk drawers, they are dressed sloppy and most of them are still improving their study discipline when they are about to take tests or exams that they will face. The type of research used by researchers is a qualitative method with the approach that will be taken is a qualitative approach. This research method approach uses a type of descriptive research approach that attempts to describe a symptom, an event that occurs when the researcher makes observations at the place to be studied. The results of the analysis of the implementation of learning discipline at SD Negeri 01 Limbangan Kersana Brebes have not been implemented well. There are still students who come late to school when learning first starts and after the break so that students' enthusiasm for learning is running low. The factors that influence the learning skills possessed by students are the differences in character possessed by students. The differences in character possessed by students mean that teachers must be able to apply or use different approach methods with students so that students can improve their learning discipline. The punishments given by teachers to students who violate them include watering the plants, cleaning the school environment and writing a statement so that they don't do it again.